Bacterial chromosomal mobility via lateral transduction exceeds that of classical mobile genetic elements - Suzanne Humphrey (Nature Portfolio, 2021)
It is commonly thought that horizontal transfer of most bacterial chromosomal genes is limited, in comparison with the frequent transfer of mobile genetic elements. Humphrey et al. show that, actually, phage-mediated lateral transduction of core chromosomal genes can be more efficient than the transfer of mobile genetic elements via conjugation or generalized transduction.